PENGARUH PENERAPAN SISTEM INFORMASI PEMERINTAH DAERAH DAN KINERJA PEGAWAI TERHADAP EFEKTIVITAS PENGELOLAAN KEUANGAN DAERAH PADA BADAN PENGELOLA KEUANGAN DAN PENDAPATAN DAERAH PROVINSI JAMBI - Prayogo, Galang Dimas; Tan, Syamsurijal; Bahri, Zainul (Jambi Accounting Review (JAR), 2025)
This study aims to determine and analyze the impact of SIPD implementation and employee performance on the regional financial management process, as well as to identify and analyze the strategies implemented by the Jambi Province Regional Financial and Revenue Management Agency (BPKPD) to improve the effectiveness of SIPD in regional financial management. The population of this study was all employees at the Jambi Province Regional Financial and Revenue Management Agency (BPKPD) involved in the use of SIPD. The total sample size was 60 respondents, using a saturated sampling technique, comprising agency heads, division heads, sub-division heads, and staff. Data analysis was performed using multiple linear regression with the help of SPSS version 20 and a SWOT analysis. The results indicate that the implementation of a regional government information system and employee performance have a positive effect on the effectiveness of regional financial management. Meanwhile, the strategies generated by the SWOT analysis indicate leveraging strengths to seize opportunities, and leveraging strengths to capitalize on opportunities.